THE URBAN DENSITY AND ISOPRICE PERSPECTIVES FOR TRANSPORTATION INFRASTRUCTURE - Ferry Hermawan (Diponegoro University, 2011)
The endownment problems of urban growth is the density. Based on Land-Rent theorema, the people move tosuburban area. After that, the access built to accommodating the people activities. This article describe aboutthe density, road network pattern identification and the isoprice as the new approach to chapturing themacroscopic evaluation. By literature study from previews study and spatial methodology by geographicinformation system, the problems was simulated quantitatively. The result of this study indicated that SemarangCity has radial concentric topology with pattern of density commencing to south district with cheaper costtransport in the dense network of public transport.